Biaxial strength and slow crack growth in porous alumina with silica sintering aid. Issue 2 (February 2018) - Bakken, Astrid; Wagner, Susanne; Hoffmann, Michael J.; Thorstensen, Bernt; Einarsrud, Mari-Ann; Grande, Tor
Abstract: Biaxial strength, fracture toughness and subcritical crack growth are reported for coarse grained porous alumina ceramics. The materials were prepared with a varying amount of a silica sintering aid, which resulted in the formation of a glassy secondary phase at the grain boundaries. Crystalline mullite was additionally found in the material with the highest silica content. The biaxial strength, measured by Ball-on-Ring and Ball-on-3-Balls, was highest for the material without mullite at the grain boundaries, and the biaxial strength decreased with increasing porosity. The fracture toughness of the materials was in the range of 1.7–1.9 MPa m 0.5 . Measurements of subcritical crack growth by a modified lifetime method in air and aqueous environments demonstrated a higher crack growth rate in water and acid relative to in air. The effect of porosity and grain boundary phase were discussed in relation to subcritical crack growth and fracture mode in the coarse grained alumina ceramics.